PENERAPAN HUKUMAN MATI BAGI PELAKU KEJAHATAN KORUPSI DI INDONESIA: ANALISIS PENDEKATAN TEORI MAQÀSHID AL-SYARÌ’AH - Khaeron Sirin (istinbath, 2013)
Corruption is a serious crime in Indonesia that has destroyedthe foundation of the state and nation. Not only is corruptiondetrimental to the state, but it also snatches social rights and economicdevelopments in general. This crime is very difficult to eradicate,because it is often committed through a systematic way and involvedthe people who hold economic and political power. The impactsof corruption are devastating. It is time now to classify corruptionan extraordinary crime that needs an extra effort, comprehensiveapproach and systematic way to eradicate it. One way to do this is byimposing death penalty to corruptors.